Isolation and Characterization of Pb Resistant Bacteria from Cilalay Lake, Indonesia - Kesi Kurnia; Nina Hermayani Sadi; Syafitri Jumianto (Graduate Program of Syiah Kuala University, 2015)
Pollution of water environment with heavy metals is becoming one of the most severe environmental and human health hazards. Lead (Pb) is a major pollutant and highly toxic to human, animals, plants, and microbes. Toxic metals are difficult to remove from the environment, since they cannot be chemically or biologically degraded and are ultimately indestructible. Biological approaches based on metal-resistant microorganisms have received a great deal of attention as alternative remediation processes. This study aim to isolate and characterize Pb resistant of heterotrophic bacteria in Cilalay Lake, West Java, Indonesia. The water samples were collected along three points around Cilalay Lake. Water physical and chemical determination was performed using the Water Quality Checker. The bacterial isolates were screened on Triptone Glucose Yeast (TGY) agar plates. Afterwards selected isolates were grown on Nutrient Agar media 50% with supplemented Pb 100 ppm by the standard disk. Population of resistant bacteria was counted. The result from metal resistant bacteria indicated that all isolates were resistant. The most abundant type of resistant bacteria to lead was Gram negative more than Gram positive. Identified have metal resistant bacteria could be useful for the bioremediation of heavy metal contaminated sewage and waste water